2015
DOI: 10.1002/mus.24520
|View full text |Cite
|
Sign up to set email alerts
|

Stroke‐related effects on maximal dynamic hip flexor fatigability and functional implications

Abstract: Introduction Stroke-related changes in maximal dynamic hip flexor muscle fatigability may be more relevant functionally than isometric hip flexor fatigability. Methods Ten subjects with chronic stroke performed 5 sets of 30 hip flexion maximal dynamic voluntary contractions (MDVC). A maximal isometric voluntary contraction (MIVC) was performed before and after completion of the dynamic contractions. Both the paretic and non-paretic legs were tested. Results Reduction in hip flexion MDVC torque in the paret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(35 reference statements)
2
7
0
Order By: Relevance
“…Fatigability can limit exercise performance, ergonomic tasks and daily activities, more so in older adults, those with chronic disease or disability such as stroke and multiple sclerosis [e.g. (56, 87). ] However, whether the sex differences in fatigability observed in healthy people are relevant to clinical populations is relatively unexplored, with some evidence for differences in people with multiples sclerosis and stroke.…”
Section: Sex Differences In Fatigability Among Clinical Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigability can limit exercise performance, ergonomic tasks and daily activities, more so in older adults, those with chronic disease or disability such as stroke and multiple sclerosis [e.g. (56, 87). ] However, whether the sex differences in fatigability observed in healthy people are relevant to clinical populations is relatively unexplored, with some evidence for differences in people with multiples sclerosis and stroke.…”
Section: Sex Differences In Fatigability Among Clinical Populationsmentioning
confidence: 99%
“…This is especially true among clinical populations (56). Determining the relevance of the laboratory-based tasks and fatigability that limit both sexes in ergonomic tasks and daily activities will provide insight to offset potential injury and disorder in men and women.…”
Section: Increasing An Understanding Of Sex Differences In Performmentioning
confidence: 99%
“…In both men and women with stroke, recent evidence demonstrates that the limb muscles are more fatigable than healthy controls [ 6 , 7 ]. Fatigability can be quantified as the acute, exercise-induced reduction in maximal force or power of a muscle or the time to failure (task duration) of a submaximal intensity task [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fatigability can be quantified as the acute, exercise-induced reduction in maximal force or power of a muscle or the time to failure (task duration) of a submaximal intensity task [ 8 ]. This greater neuromuscular fatigability with stroke compared with healthy controls was observed as a larger reduction in maximal dynamic voluntary contractions [ 6 ] and a reduced time to failure of sustained isometric contractions [ 7 ]. Accordingly, we have shown that fatigability of the hip flexor muscles is associated with walking speed in people with stroke [ 6 ], so that people with stroke who have greater hip flexion fatigability have larger decrements in walking performance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation